2013
DOI: 10.1111/1469-0691.12091
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia due to OXA-48-carbapenemase-producing Enterobacteriaceae: a major clinical challenge

Abstract: Bacteraemia due to carbapenemase-producing Enterobacteriaceae is an emerging medical problem. Management of this entity is complicated by the difficulty in identifying resistance patterns and the limited therapeutic options. A cohort study was performed including all episodes of bloodstream infection due to OXA-48-producing Enterobacteriaceae (O48PE), occurring between July 2010 and April 2012. Data on predisposing factors, clinical presentation, therapy and outcome were collected from medical records. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 28 publications
4
75
1
2
Order By: Relevance
“…Twenty studies met the inclusion criteria (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The detailed search process and study selection are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies met the inclusion criteria (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The detailed search process and study selection are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported on carbapenemase-producing Enterobacteriaceae (9,10,12,14,16,17,(19)(20)(21)(22)(23)(25)(26)(27)(28) and five others on carbapenem-resistant Enterobacteriaceae (11,13,15,18,24). One study included infections due to carbapenem-resistant K. pneumoniae isolates, mainly isolates that produced KPC (11).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that carbapenems should be included in treatment regimens for OXA-48 containing strains that have low meropenem or imipenem MICs. 70,71 KPC and some OXA-48 carbapenemases are inhibited by ceftazidime-avibactam, which may be a therapeutic option for strains expressing these enzymes. However, this drug does not have activity against the class B metallo-b-lactamases (such as NDM), 72 and resistance in at least one KPC-producing K. pneumoniae has been described.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%
“…[65][66][67] There is more evidence that fosfomycin is useful in UTIs caused by other highly resistant b-lactamase producing gram-negative bacilli, including ESBLproducing organisms. 68 The limited bioavailability makes giving oral fosfomycin problematic for systemic CRE infections.…”
Section: Fosfomycinmentioning
confidence: 99%